Adolescent Patient's Perceptions During Treatment With Class II Elastics - V. Bogdanov; D. Ilova; Gr. Yordanova (Hindawi Limited, 2024)
The article presents a case of a 13-year-old adolescent male patient who started orthodontic treatment at the age of 12. Before treatment, he was diagnosed with narrow maxilla, proclination of upper incisors, deep overbite, distal occlusion bilaterally with significant sagittal overjet in frontal area, skeletal Class II, and hypodivergent growth pattern. During treatment, the patient is in his pubertal growth spurt. About 2 months after intermaxillary Class II elastics (1/4 heavy, 6.5 Oz) were applied, he complained of pain during mastication, wide opening of the mouth, and sometimes during protrusive and lateral movements in the right TMJ. The TMJ X-ray examination did not reveal abnormal morphological changes. Occlusion was evaluated by an electromyographic device, Teethan. The result was typical for Class II malocclusion. During the bilateral palpation of the zones of TMJ and opening of the mouth and chewing, the patient reported pain on the right side. There was no clicking in the joint. The elastic wear was stopped, and soon afterwards, the pain disappeared. These complaints point to a possible relationship between orthodontic treatment and TMJ pain. However, the disappearance of complaints after the removal of the Class II elastics points that the temporomandibular joint disorder (TMD) symptoms are reversible and resolved.